Synthesis and biological activity of novel mono-indole and mono-benzofuran inhibitors of bacterial transcription initiation complex formation. Issue 8 (15th April 2015) - Mielczarek, Marcin; Thomas, Ruth V.; Ma, Cong; Kandemir, Hakan; Yang, Xiao; Bhadbhade, Mohan; Black, David StC.; Griffith, Renate; Lewis, Peter J.; Kumar, Naresh
Graphical abstract: Abstract: Our ongoing research focused on targeting transcription initiation in bacteria has resulted in synthesis of several classes of mono-indole and mono-benzofuran inhibitors that targeted the essential protein–protein interaction between RNA polymerase core and σ 70 / σ A factors in bacteria. In this study, the reaction of indole-2-, indole-3-, indole-7- and benzofuran-2-glyoxyloyl chlorides with amines and hydrazines afforded a variety of glyoxyloylamides and glyoxyloylhydrazides. Similarly, condensation of 2- and 7-trichloroacetylindoles with amines and hydrazines delivered amides and hydrazides. The novel molecules were found to inhibit the RNA polymerase– σ 70 / σ A interaction as measured by ELISA, and also inhibited the growth of both Gram-positive and Gram-negative bacteria in culture. Structure–activity relationship (SAR) studies of the mono-indole and mono-benzofuran inhibitors suggested that the hydrophilic–hydrophobic balance is an important determinant of biological activity.